Social Movements, Cultural Memory and Digital Media
XX, 298 p. 14 illus.
Keywords: This collected volume is the first to study the interface between contemporary social movements, cultural memory and digital media. Establishing the digital memory work practices of social movements as an important area of research, it reveals how activists use digital media to lay claim to, circulate and curate cultural memories. Interdisciplinary in scope, its contributors address mobilizations of mediated remembrance in the USA, Germany, Sweden, Italy, India, Argentina, the UK and Russia.